1993
DOI: 10.1210/jcem.76.6.8501149
|View full text |Cite
|
Sign up to set email alerts
|

The thyrotropin receptor (TSH-R) is not an oncogene for thyroid tumors: structural studies of the TSH-R and the alpha-subunit of Gs in human thyroid neoplasms.

Abstract: The development and progression of thyroid tumors are associated with phenotype-specific mutations of genes involved in growth control. Thyroid cell growth is controlled in part by the interaction of TSH with its receptor, with subsequent activation of the GTP-binding protein and its effector, adenylyl cyclase. The resulting increase in intracellular cAMP stimulates growth in thyrocytes. The TSH receptor (TSH-R) is a seven-transmembrane domain receptor. Intracellular domains of the TSH-R important for signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…An argument against its involvement in tumour initiation is the lack of TSH receptor mutations interfering with signal transduction in thyroid carcinomas (Matsuo et al 1993). Furthermore, thyroid carcinomas can occur in patients with a range of serum TSH, including in those who take exogenous thyroid hormones and have suppressed serum TSH concentrations for treatment of other thyroid diseases (Satta et al 1993).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…An argument against its involvement in tumour initiation is the lack of TSH receptor mutations interfering with signal transduction in thyroid carcinomas (Matsuo et al 1993). Furthermore, thyroid carcinomas can occur in patients with a range of serum TSH, including in those who take exogenous thyroid hormones and have suppressed serum TSH concentrations for treatment of other thyroid diseases (Satta et al 1993).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…First, TSH receptor mutations in regions functionally associated with increased signal transduction do not commonly occur in thyroid carcinomas (Matsuo et al 1993). Second, in vitro studies have shown that other growth factors such as insulin-like growth factor-I (IGF-I) have been shown to be more potent in stimulating thyroid cancer growth (Derwahl et al 1999, Mazzaferri 2000, and TSH requires cooperation with insulin/IGF-1 to exert its proliferative effects (Kimura et al 2001).…”
Section: The Tsh Receptor In Benign and Malignant Thyroid Tumoursmentioning
confidence: 99%
“…The 5th-6th TMDs (TM5-TM6) and the 3rd extracellular loop regions of the TSHR have most of the activating mutations. It is intriguing that the TSHR was thought of as a candidate oncogene for thyroid tumors, although structural studies did not support this view (79). However, Fournes et al (80) examined the oncogenic potential of a mutant hTSHR or Gsa expressed in rat FRTL-5 cells, and showed that only the mutant TSHR was able to induce neoplastic transformation, as demonstrated by growth in semi-solid medium and tumorigenesis in nude mice.…”
Section: The Tshr Gene and Thyroid Neoplasmsmentioning
confidence: 99%